Bis[5-bromo-1 H-indole-3-carbaldehyde (2-nitro-benzoyl)hydrazonato- κ2N,O]bis(pyridine-κ:N)-nickel(II) pyridine disolvate - Ali, Hapipah Mohd; Ng, S.W.; Halim, A.; Nadiah, S. (International Union of Crystallography, 2005)
The Ni atom in the crystal structure of the title compound, [Ni(C 5H5N)2(C16H10)BrN 4O3)2]·2C5H5N, lies on a special position of site symmetry 2 in an all-cis octahedral geometry. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.